Designing web sites that work : usability for the Web - Brinck, Tom.; Gergle, Darren; Wood, Scott D. (San Francisco : Morgan Kaufmann Publishers, 2002)
Every stage in the design of a new web site is an opportunity to meet or miss deadlines and budgetary goals. Every stage is an opportunity to boost or undercut the site's usability. This book tells you how to design usable web sites in a systematic process applicable to almost any business need. You get practical advice on managing the project and incorporating usability principles from the project's inception. This systematic usability process for web design has been developed by the authors and proven again and again in their own successful businesses. A beacon in a sea of web design titles, this book treats web site usability as a preeminent, practical, and realizable business goal, not a buzzword or abstraction. The book is written for web designers and web project managers seeking a balance between usability goals and business concerns. * Examines the entire spectrum of usability issues, including architecture, navigation, graphical presentation, and page structure. * Explains clearly the steps relevant to incorporating usability into every stage of the web development process, from requirements to tasks analysis, prototyping and mockups, to user testing, revision, and even postlaunch evaluations. * Includes forms, checklists, and practical techniques that you can easily incorporate into your own projects at http://www.mkp.com/uew.
ch. 1. Usability throughout the design process -- ch. 2. Target audience and target platforms -- ch. 3. User needs analysis -- ch. 4. Task analysis -- ch. 5. Information architecture -- ch. 6. Page layout -- ch. 7. Envisioning design -- ch. 8. Writing for the web -- ch. 9. Design elements -- ch. 10. Usability in software development -- ch. 11. Pre-launch and post-launch -- ch. 12. Usability evaluation.
Περιέχει βιβλιογραφικές παραπομπές και ευρετήριο.
Keywords: Web sites -- Design; Computer software -- Human factors; Sites Web -- Conception; Ιστότοποι -- Σχεδιασμός.; Λογισμικό υπολογιστών.